Acute care model that reduces oncology-related unplanned hospitalizations to promote quality of care and reduce cost. (September 2019) - Coyle, Yvonne M.; Ogola, Gerald O.; MacLachlan, Carl R.; Hinshelwood, Margaret M.; Fleming, Neil S.
Highlights: Acute hospital-based care can be high cost and potentially lower quality of care. Unplanned hospitalizations are potentially preventable. Evidence-based acute care decreased unplanned oncology hospitalization and cost. Abstract: Background: Advances in cancer treatment has resulted in more oncology patients receiving outpatient therapy; however, this can promote a greater use of costly hospital-based acute care. Methods: The Oncology Evaluation and Treatment Center (OETC) was established in March 2012 at Baylor University Medical Center (BUMC), a large urban hospital, as a quality improvement intervention to reduce oncology patient acute care and cost. The OETC provides after-hours acute care for oncology patients receiving outpatient care at BUMC. OETC care included optimal use of evidence-based cancer supportive care. The intervention group included oncology patients who accessed the OETC and potentially BUMC emergency department (ED) during the study period. The control group included oncology patients who only accessed BUMC ED during this time. March 1, 2012 through June 30, 2018, a total of 8335 unique oncology patients utilized the BUMC inpatient and outpatient settings (OETC and ED) for acute care. Results: Oncology-related unplanned hospitalizations per 100 outpatient visits were lower in the intervention versus control group (27·3 versus 32·7, P < 0·0001). Furthermore, there was no difference in the average annual cost for outpatient acute care (OETC and ED) between the two groups (6368 versus 6, 593, P = 0·35), but the cost was lower for oncology-related unplanned hospitalizations in the intervention group (62, 260 versus 81, 911, P < 0·0001). This translated to 19, 651 annual savings for unplanned hospitalizations for the intervention group. Conclusions: Providing optimal use of evidence-based cancer supportive care to oncology patients in a dedicated acute care setting decreased oncology-related unplanned hospitalizations and related costs.